Systematics of Indo-Pacific fireflies with a redefinition of Australasian Atyphella Olliff, Madagascan Photuroluciola Pic, and description of seven new genera from the Luciolinae (Coleoptera: Lampyridae) - Ballantyne, Lesley A.; Lambkin, Christine (Zootaxa, 2009)
This major systematic revision of fireflies (Coleoptera: Lampyridae) concentrates on the genera related to Atyphella Olliff in the Luciolinae. Seven new genera and 19 new species are described, which with two exceptions occur in the area encompassed by Australia, the Republic of Palau, Federated States of Micronesia, Papua New Guinea, Indonesia (West Irian), Solomon Islands, New Caledonia, Vanuatu and Fiji. Keys to the genera and subgenera of the Luciolinae are included. The revision is based upon a phylogenetic analysis of 343 morphological characters of males, females and larvae of 112 Luciolinae species, including the type species of the six genera and four subgenera of the Luciolinae sensu McDermott (1966). The genus Atyphella Olliff is redefined and redescribed from 23 species including 14 endemic Australian species, and nine species from the wider study area. A. leucura Olivier, A. scabra Olivier and A. testaceolineata Pic are redescribed. A. palauensis Wittmer is elevated to species level from A. carolinae palauensis Wittmer and redescribed. Aquilonia gen. n. is described for Aq. costata (Lea), transferred from Atyphella Olliff. Convexa gen. n. is described for C. wolfi (Olivier), transferred from Atyphella. Gilvainsula gen. n. includes the new species, G. similismessoria sp. n., and G. messoria (Olivier), transferred from Atyphella Olliff. Lloydiella gen. n. includes four species; Ll. majuscula (Lea) transferred from Atyphella, and three new species, Ll. japenensis sp. n., Ll. uberia sp. n., and Ll. wareo sp. n. Pygatyphella (Ballantyne) is elevated to generic status from Luciola (Pygatyphella) Ballantyne and redescribed from 22 species including ten new species Pygat. japenensis sp. n., Pygat. karimui sp. n., Pygat. kiunga sp. n., Pygat. limbatifusca sp. n., Pygat. nabiria sp. n., Pygat. okapa sp. n., Pygat. russellia sp. n., Pygat. tomba sp. n., Pygat. uberia sp. n., and Pygat. wisselmerenia sp. n., with uberia representing specimens known in previous analyses as ‘Sisiak’. Pygat. eliptaminensis (Ballantyne), Pygat. marginata (Ballantyne), Pygat. peculiaris (Olivier) and Pygat. pulcherrima (Ballantyne) are transferred from Luciola (Pygatyphella) Ballantyne. Pygat. tagensis (Ballantyne), Pygat. hounensis (Ballantyne), Pygat. obsoleta (Olivier), and Pygat. undulata (Pic) are transferred from Atyphella Olliff; Pygat. obsoleta is reassessed, geographic varieties are suggested, and the species redescribed from a greatly expanded number of specimens. Pygat. ignota (Olivier), Pygat. plagiata (Blanchard) and Pygat. salomonis (Olivier) are transferred from Luciola Laporte and redescribed. Pygat. limbatipennis (Pic) is transferred from Atyphella salomonis var limbatipennis Pic, and redescribed. Magnalata gen. n. is described for three species, M. rennellia sp. n., M. limbata (Blanchard) transferred from Luciola, and M. carolinae (Olivier) transferred from Atyphella. Missimia gen. n. is erected for a single species M. flavida sp. n. based on four specimens dealt with in previous phylogenetic analyses as ‘Mt Missim’. Photuroluciola Pic is elevated to generic status from Luciola (Photuroluciola) Pic and redescribed from its single species Photuro. deplanata Pic. Asymmetricata gen. n. is erected for two SE Asian species As. ovalis (Hope) and As. circumdata (Motsch.), both transferred from Luciola and redescribed. Where available, females are associated and are characterised briefly. A. testaceolineata, M. limbata, Pygat. huonensis, Pygat. limbatipennis, Pygat. peculiaris, and Pygat. uberia sp. n. are identified by light patterns. Discussion addresses: the interpretation of female aptery, the extent of the labrum, numbering of abdominal segments using actual segment number, and use of the term ventrite to reflect visible abdominal sternites. Functional morphology of many terminal abdomen modifications is addressed as is the range and nature of colour patterns. Determination of polarity in various states of bipartite light organs is overviewed, as are problems with the homology of characters, and difficulties in interpretation of characters in soft bodied insects especially those preserved in ethanol.